Origin of the Large Entropy Change in the Molecular Caloric and Ferroelectric Ammonium Sulfate (Adv. Funct. Mater. 45/2022). (3rd November 2022) - Yuan, Shurong; Meijer, Bernet E.; Cai, Guanqun; Dixey, Richard J. C.; Demmel, Franz; Dove, Martin T.; Liu, Jiaxun; Playford, Helen Y.; Walker, Helen C.; Phillips, Anthony E.
Abstract : Molecular Caloric In article number 2207717, Phillips and co‐workers show that the large entropy change in the caloric material ammonium sulfate arises from librations of the ammonium ions in flat‐bottomed, "bathtub‐shaped" potential wells rather than an order‐disorder phase transition. Engineering similar energy landscapes may be a promising route to designing new caloric molecular materials.